62 Biventricular evaluation of gliflozines effects in chronic heart failure patients function (begin-HF study): an international registry. (8th December 2021) - Correale, Michele; Mazzeo, Pietro; Petroni, Renata; Coiro, Stefano; Antohi, Elena-Laura; Monitillo, Francesco; Leone, Marta; Triggiani, Marco; Dungen, Hans-Dirk; Sarwar, Chaudhry M. S.; Nodari, Savina
Abstract: Aims: Sodium glucose cotransporter type 2 (SGLT2) inhibitors represent a new class of hypoglycemic agents for type 2 diabetes mellitus (T2DM), which act independently of insulin to selectively inhibit renal glucose reabsorption, thereby increasing urinary excretion of glucose. Several studies have demonstrated the cardioprotective effects of SGLT2-i in patients with heart failure (HF), with and without diabetes mellitus. It is also unknown whether these SGLT2is-associated benefits are associated with the amelioration of left or right ventricular function in patients affected by HF with T2DM. Evaluate the effect of SGLT2 inhibitors on left and right ventricular function by conventional and advanced echocardiographic parameters, focusing on speckle tracking echocardiography, in patients with HF and T2DM. Methods and results: BEGIN-HF is an international multi-centre registry enrolling outpatients affected by HF and T2DM. Inclusion criteria are HbA1c> 6.5%, eGFR [MDRD] > 45 ml/min/1.73 m 2, age > 18 years, FE < 50%. Exclusion criteria are type 1 diabetes mellitus (T1DM), previous amputation surgery, recurrent urinary tract infections. For each patient medical history, clinical and biochemistry data will be collected, starting treatment with SGLT2 inhibitors will be included. All patients will undergo conventional, TDI, and strain echocardiography in an ambulatory setting, at the enrollement and after 3 and 6 months. The patients will be divided in the two subgroup for analysis (patients starting SGLT2i therapy and patients no starting SGLT2i). The primary endpoint will be the improvement of LV systolic and right ventricular systolic function as assessed by conventional, TDI and myocardial deformation speckle tracking parameters. A univariate and multivariate analysis will be performed to search for predictors of improvement of systolic function. Conclusions: This is the first international multicentre registry evaluating biventricular function by conventional and advanced echocardiography in patients with HF and T2DM starting and no-starting SGLT2i therapy.